Pengaruh Lama Simpan Pada Suhu Dingin Terhadap Mutu Organoleptik Dan Hedonik Susu Pasteurisasi - Sosiawati, Endang Sapta Hari; Rahmawati, Nurina (Jurnal Ilmiah Fillia Cendekia, 2024)
The importance of doing this research is for the basis of business applications. Field reality shows that the shelf life of pasteurized milk is relatively short, causing many losses. The aim of the study was to determine the effect of long storage of pasteurized milk at cold temperatures (4oC) on organoleptic and hedonic qualities. The research method used was the experimental method, with a completely randomized design (CRD 7x4). Treatment of 7 pieces (H0 - H6) with 4 repetitions. Research variables: organoleptic quality and hedonic quality, indicators used: color, aroma, texture and taste tested by quality test. In this test, 25 untrained panelists were used per treatment observation. The amount of pasteurized milk used was 1000 mL. Data analysis was carried out using the ANOVA test and if there was a significant or very significant difference, then it was continued with the Duncan test. The results showed that storage time at cold temperatures (40C) had no significant effect (P>0.05) on the organoleptic and hedonic qualities which included color, aroma, texture and taste.